Comparing Litigation and Arbitration Approaches to Resolving Export-Import Business Disputes in Indonesia - Arnold, Arnold (Jurnal Ilmu Hukum Kyadiren, 2025)
Export-import business disputes pose significant challenges in the global trade landscape. This research examines the critical factors influencing dispute resolution methods, specifically comparing litigation and arbitration in international trade contexts. Through a normative legal research methodology with a comparative approach, the study analyzes the advantages and limitations of each method. Key considerations include dispute complexity, monetary value, confidentiality requirements, party dynamics, and potential impacts on business relationships. The findings reveal that arbitration often provides more flexible, efficient, and relationship-preserving resolution compared to traditional litigation, though the optimal approach depends on specific case circumstances. The research provides strategic insights for businesses navigating international trade conflicts, emphasizing the importance of nuanced dispute resolution strategies.